Are you over 35 and have no children? If you live in Southern Europe, know your chances of remaining childless. - Freitas, Rita (2019)
Low fertility is one of the main concerns in Europe, especially in Southern European countries, which were affected by the most recent economic and financial crisis. The increasing number of men and women who choose to remain without children and the continuous postponement of fertility projects have contributed to the low fertility levels observed in recent years across Europe. Despite the already studied effects of fertility postponements, we know little about Southern Europeans’ reproductive intentions after age 35, age from which it is considered that those who have no children, or have only one child, have postponed their fertility projects.